2015
DOI: 10.1159/000380885
|View full text |Cite
|
Sign up to set email alerts
|

Role of Host-Derived Proteinases in Dentine Caries and Erosion

Abstract: Demineralization in dentinal caries and erosion exposes dentine organic matrix. This exposed matrix, containing type I collagen and non-collagenous proteins, is then degraded by host collagenolytic enzymes, matrix metalloproteinases (MMPs) and cysteine cathepsins. The knowledge of the identities and function of these enzymes in dentine has accumulated only within the last 15 years, but has already formed a field of research called ‘dentine degradomics'. This research has demonstrated the role of endogenous col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 59 publications
0
47
0
9
Order By: Relevance
“…Recent studies have demonstrated that endogenous dentinal and salivary MMP can play a major role in dentinal caries and erosion pathology [Tjä-derhane et al, 1998;van Strijp et al, 2003;Buzalaf et al, 2015;Tjäderhane et al, 2015]. At least MMP-2, MMP-3, MMP-8, MMP-9, and MMP-20 have been indicated to participate in the process of dentin caries [Tjäderhane et al, 1998;Sulkala et al, 2002;Vidal et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that endogenous dentinal and salivary MMP can play a major role in dentinal caries and erosion pathology [Tjä-derhane et al, 1998;van Strijp et al, 2003;Buzalaf et al, 2015;Tjäderhane et al, 2015]. At least MMP-2, MMP-3, MMP-8, MMP-9, and MMP-20 have been indicated to participate in the process of dentin caries [Tjäderhane et al, 1998;Sulkala et al, 2002;Vidal et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…The supersaturation is defined as σ = ln ((αCa 2+ ) 5 (αPO 4 3− ) 3 (αOH − )/ Ksp ), where α denotes the species activity, and Ksp denotes the equilibrium solubility constant at 25°C. This supersaturated (σ = 3.34) calcium phosphate solution was made by mixing 13.5 mM of CaCl 2 ·H 2 O with 6.3 mM of K 2 HPO 4 in equal volumes to achieve [Ca 2+ ]=6.75 mM and [HPO 4 2− ]=3.15 mM.…”
Section: Methodsmentioning
confidence: 99%
“…As caries penetrate the outer enamel, which contains little or no organic matrix, it begins to demineralize the underlying dentin, which consists of hydroxyapatite (HAP) nanocrystals located within collagen fibrils (intrafibrillar) and between collagen fibrils (extrafibrillar) 2 . The bacterial attack is also accompanied by the release of bacterial and endogenous proteases in dentin, which leads to hydrolysis of the collagen scaffold as well as the NCPs 3 . When remineralization is attempted, the absence of NCPs inhibits the development of intrafibrillar HAP.…”
Section: Introductionmentioning
confidence: 99%
“…Dentin itself is also known to contain proteases, such as MMP-2, 3, 8, 9, and 20, and cysteine cathepsins B and K [Sulkala et al, 2002;Mazzoni et al, 2009;Shimada et al, 2009;Toledano et al, 2010;Boushell et al, 2011;Buzalaf et al, 2015;Tjäderhane et al, 2015]. These proteases are produced during dentin formation and then become embedded in the dentin matrix (in their inactive forms) together with protease inhibitors, such as tissue inhibitor of metalloproteinases (TIMP)-1 and -2 [Ishiguro et al, 1994;Niu et al, 2011].…”
Section: Protein Degradation By Host-and Bacteria-derived Proteasesmentioning
confidence: 99%